Modern Acetylene Hydrochlorination Catalysts - Rakhmatov Doniyor Khudayorovich; Abdullaev Bakhtishod Menglikul angles; Norboev Farrukh Abdumalikovich; Makhkamov Bakhrom Azimzhonovich (Zien Journals, 2021)
The paper presents the results of the analysis of patent literature on the development of mercuryfree catalysts for the process of hydrochlorination of acetylene. Catalysts based on gold chloride and base metal chlorides are considered, and a comparative analysis of these catalysts is carried out.
Keywords: vinyl chloride; acetylene hydrochlorination; gold chloride; acetylene